Longitudinal study of mental health in an elite soccer club: Depression and anxiety symptoms across a competitive season - Bürger, L.; Reis, D.; Spielmann, J.; Mayer, J.; Steindorf, L. (Psychology of Sport and Exercise, 2025)
In high-performance sports, recognition of mental health's significance is growing. However, due to a lack of comprehensive longitudinal studies, the time course and stability of athletes` mental health throughout a competitive season remains unclear. The present work aimed to address this gap by assessing depression and anxiety symptoms at four measurement points during a season using the Center for Epidemiologic Studies Depression Scale and the Generalized Anxiety Disorder Screener. The study involved N = 204 youth and professional soccer players (79% male, Mage = 16.13, SDage = 4.17) of a German Bundesliga club. Over the study period, several players reported experiencing depressive (12.7%) and anxiety symptoms (15.6%) exceeding clinical thresholds at least once. Further analyses revealed significant fluctuations in mental health over the season. Depressive symptoms showed a linear increase, possibly indicating the taxing nature of a soccer season. Anxiety symptoms showed a moderate increase at the beginning of the second half of the season and decreased as the season progressed towards its end. Further, female players reported higher levels of depression and anxiety symptoms compared to male players. Regarding the stability of symptoms across the competitive season, the variance decomposition of latent-state-trait models revealed that the stable components (i.e., the consistent characteristics that remain stable over time) were larger than the unstable components (i.e., the measurement-dependent differences that change depending on the time point). Our findings thus endorse the allocation of resources towards long-term, customized mental health interventions for vulnerable players to mitigate psychological issues in high-performance soccer.